Higher Expression of Epidermal Growth Factor Receptor Is Associated with Extracellular Matrix Metalloprotease Inducer in Colorectal Adenocarcinoma: Tissue Microarray Analysis of Immunostaining Score with Clinicopathological Parameters. Issue 5 (9th June 2013) - Jin, Jong-Shiaw; Wu, Chi-Ying; Lin, Yeh-Feng; Wang, Jia-Yi; Yu, Cheng-Ping; Sheu, Lai-Fa; Chiang, Hung; Tsai, Wen-Chiuan; Lee, Wei-Hwa
Abstract : Aim : Extracellular matrix metalloprotease inducer (EMMPRIN) expression was demonstrated in several cancers, but its expression profile in colorectal cancers remains unclear. Epidermal growth factor receptor (EGFR) was reported to regulate EMMPRIN expression in human epithelial cancers. Our purpose was to determine EMMPRIN expression and its relationship with EGFR in colorectal cancers. Methods : Immunohistochemical analysis of EMMPRIN and EGFR was performed in tissue microarray slides of 90 surgical specimens including 32 well differentiated, 35 moderately differentiated, and 23 poorly differentiated colorectal adenocarcinomas. Results : All colorectal adenocarcinomas showed significant immunohistochemical expression of EMMPRIN. The EMMPRIN scores in poorly differentiated (303 ± 21) and moderately differentiated (326 ± 17) colorectal adenocarcinoma were significantly higher than in well differentiated (166 ± 20) colorectal adenocarcinoma. EGFR expression was mainly on the cell surface of tumor cells and the immunostaining scores of EGFR were significantly associated with the advanced clinical T and N stages. A significantly positive relationship between EMMPRIN and EGFR immunostaining scores was also noted. Conclusions : Increased expression of EMMPRIN and EGFR in colorectal adenocarcinomas is associated with clinicopathological parameters of advanced colorectal adenocarcinoma stages. In addition, the data from this study support the notion that EGFR expression may up-regulate EMMPRIN expression .